STRATEGI DAN TANTANGAN GURU DALAM MENINGKATKANKEMAMPUANMEMBACAPADASISWAKELAS1SDNEGERI1BAWUKABUPATENJEPARA - Ilman Hanafi Destian (Tunas Nusantara, 2021)
Reading skills are one of the language skills that a person must possess, especially grade 1elementary school students. So to improve reading skills the teacher must implement effective andefficient strategies. This study aims to analyze the form of learning strategies to improve students'reading skillsand the obstaclesand challengesfaced in implementing these strategies.Themethod used in this research is descriptive qualitative research method in which data collectionuses interview techniques, observation and documentation. This research was conducted at SDNegeri 1 Bawu Jepara. The results showed that the teacher's strategy in improving students'reading skills was by providing additional lessons called "Reading Lessons" in which the teacherapplied several methods and used several learningmedia.Firstuse letter card media.Bothreading books are bound by adopting the iqro 'method. Third, cultivate a sense of joy in learning bysinging. Fifth, using the reading aloud method. Then the obstacles that the teacher encountered inimprovingstudents'readingskillswerethecharacteristicsofstudentswhowerestillinthetransitional period, a class atmosphere that was not conducive, and limited reading books. Basedon the results of this study, the use of the "Reading Lessons" strategy was able to help studentsimprovetheirreading skills.Keywords:Strategy,Improvement,Reading,ElementarySchool